2011
DOI: 10.17221/121/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crop management upon the agronomic traits of spelt (Triticum spelta L.)

Abstract: Investigations were carried out at the experimental field of the Faculty of Agriculture in Zagreb in the growing seasons 2008/2009 and 2009/2010 with the aim to determine the influence of seeding rate and fungicide treatment upon the yield and yield components of spelt (Triticum spelta L.). The trial included two spelt cultivars: Nirvana and Ostro, three seeding rates: 200, 300, and 400 germinated seeds/m 2 , and a fungicide treatment (tebuconazole). Cultivar Nirvana produced a significantly higher grain yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…Ruiz et al [5] described some yield-related traits that have been identified as potential targets to achieve better grain yields of old wheat varieties in no-tillage and minimum tillage systems. Special attention is directed to the possible production of alternative cereals in organic production [6]. These species are nowadays rather produced for feed as alternatives to oats and barley.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruiz et al [5] described some yield-related traits that have been identified as potential targets to achieve better grain yields of old wheat varieties in no-tillage and minimum tillage systems. Special attention is directed to the possible production of alternative cereals in organic production [6]. These species are nowadays rather produced for feed as alternatives to oats and barley.…”
Section: Introductionmentioning
confidence: 99%
“…Spelt has the potential for low input production and adaptation to harsh ecological conditions and resistance to diseases [10]. Owing to its hulled grain and genetic polymorphism of its population, spelt is resistant to pests and diseases and hence suitable for organic production [6]. Spelt wheat and its products could serve as an abundant source of protein and a great proportion of soluble fibre emerging in the final spelt wheat products [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mass of 1000 grains of the filmy spelt grain is in the range of 102...117 g, and in the collapsed grain it is 41,5...57,5 g, that is, it decreases 2.0...2.5 times in accordance with the above ranges moisture changes in filmy and collapsed grain. The true volume of 1000 grains of both forms of spelled changes proportionally as many times, which in the same humidity ranges is 104...150 cm 3 and 32...44 cm 3 , respectively. Comparative differences in the studied properties of spelt are determined by the presence of flower films in filmy grain.…”
Section: ____________________________________________________________mentioning
confidence: 97%
“…Аналіз літературних джерел показав, що ряд зарубіжних [3,4] та вітчизняних авторів [5,6] досліджували деякі фізико-технологічні характеристики цих пшениць.…”
Section: ____________________________________________________________unclassified
See 1 more Smart Citation